La informalidad y la evasión tributaria de los vendedores de ropa de vestir del mercado modelo, Iquitos 2023 - Vasquez Lozano, Flavio Santos (2024)
The objective of this research was to determine the relationship between informality and tax evasion of clothing sellers in the Model Iquitos market, 2023. This research is descriptive-correlational, followed a quantitative approach, non-experimental design and cross-sectional. Two questionnaires were applied to 40 informal sellers. It was found that there is a medium positive correlation between the study variables (r=0.492; p<0.001). It was concluded that there is a significant relationship between informality and tax evasion of clothing sellers in the Model market.